Characteristics of liver transplant candidates delisted following recompensation and predictors of such delisting in alcohol‐related liver disease: a case–control study. (27th July 2017) - Aravinthan, Aloysious D.; Barbas, Andrew S.; Doyle, Adam C.; Tazari, Mahmood; Sapisochin, Gonzalo; Cattral, Mark S.; Ghanekar, Anand; McGilvray, Ian D.; Selzner, Markus; Greig, Paul D.; Bhat, Mamatha; Selzner, Nazia; et al.
Summary: Whether and when recovery beyond the need for transplant may occur in patients listed for decompensation remains unclear. This study aimed to investigate the characteristics of patients delisted following recompensation. Seventy‐seven patients who were listed between 2005 and 2015 for decompensation, but later delisted following recompensation were included. Alcohol‐related liver disease (ALD) was the underlying etiology in the majority ( n = 47, 61%). Listing characteristics of these patients were compared with those of decompensated ALD patients who either underwent deceased donor liver transplantation or died on the waiting list. The model for end‐stage liver disease (MELD) score <20 and serum albumin ≥32 g/l at listing were the only independent predictors of recompensation/delisting in ALD. The probability of recompensation was 70% when both factors were present at listing. Interestingly, about a tenth of decompensated ALD patients who died on the waiting list (median duration on waiting list 11 months) and a quarter of decompensated ALD patients who underwent living donor liver transplantation (median duration on waiting list 2 months) also had both factors at listing. In conclusion, ALD seems to be the most favorable etiology for recompensation beyond the need for transplantation. Both MELD and serum albumin at listing independently predict recompensation/delisting in ALD. It seems advisable to implement a period of observation for ALD patients with both favorable factors, before embarking on living donor liver transplantation.